2015
DOI: 10.1089/jop.2015.0029
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Cytokine-Mediated Regulation of Thrombospondin-1 and CD36 in Conjunctival Cells

Abstract: Purpose: Increased expression of transforming growth factor-b2 (TGF-b2) is reported in the conjunctiva of dry eye patients with no increase of anti-inflammatory activity of TGF-b2. Our aim was to compare the expression of molecules involved in TGF-b2 activation, thrombospondin-1 (TSP-1) and CD36, during murine and human conjunctival inflammation. Methods: Human conjunctival tissue from cadaveric donors, human conjunctival epithelial primary cells and fibroblasts, and murine conjunctivas were immunostained for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 48 publications
(60 reference statements)
1
20
0
Order By: Relevance
“…Similar to SjS patients, SjS-specific autoantibodies were detected at elevated levels in the TSP-1 2/2 mice sera. TSP-1 2/2 mice also have elevated levels of interleukins and IFN-g, and, importantly, they gradually develop severe inflammation of the LG with infiltrates containing CD4 and CD8 cells, similar to humans with SjS [14,46,47]. Analysis of Tsp-1 expression pattern in the LG showed that Tsp-1 protein is expressed at the apical surface of ductal epithelial cells (supplemental online Fig.…”
Section: Putative Epcps Engraft Into Injured and "Diseased" Lgsmentioning
confidence: 87%
“…Similar to SjS patients, SjS-specific autoantibodies were detected at elevated levels in the TSP-1 2/2 mice sera. TSP-1 2/2 mice also have elevated levels of interleukins and IFN-g, and, importantly, they gradually develop severe inflammation of the LG with infiltrates containing CD4 and CD8 cells, similar to humans with SjS [14,46,47]. Analysis of Tsp-1 expression pattern in the LG showed that Tsp-1 protein is expressed at the apical surface of ductal epithelial cells (supplemental online Fig.…”
Section: Putative Epcps Engraft Into Injured and "Diseased" Lgsmentioning
confidence: 87%
“…In addition to growth factors and anti-bacterial agents, the tear film contains T-cell-mediated anti-inflammatory agents. Transforming growth factor b is a cytokine secreted by macrophages that suppresses corneal fibroblast activity and promotes antiinflammatory activity (Soriano-Romani et al, 2015). Dietderived anti-inflammatory omega-3 lipids are released into the tear film, which enhances the replacement of ocular epithelia as well.…”
mentioning
confidence: 99%
“…It has been suggested that TGF‐β plays a role in ocular surface healing and sensitivity in corneal and conjunctival cells . Therefore, we assessed TGF‐β mRNA and TGF‐β production in HCECs cultured in high glucose.…”
Section: Discussionmentioning
confidence: 99%